PELATIHAN KEPEMIMPINAN BAGI ANGGOTA KOPERASI MAHASISWA - Berta Dian Theodora; Siti Marti’ah (Bajang Institute, 2024)
The Student Cooperative, commonly known as KOPMA, is one of the Student Activity Units at Jakarta State University which not only operates in the organizational field, but also entrepreneurship. KOPMA which functions as an Educational Laboratory and as a Business Laboratory is a place to channel students' interests and talents in organizing and a place to apply the knowledge gained in lectures. KOPMA hold Basic Level Cooperative Training activities for all members and administrators. This activity was held so that members and administrators of KOPMA have strong cooperative knowledge, have an entrepreneurial and a leadership spirit that will be useful for their future lives. This activity is carried out starting from the Introduction, Pre and Basic Level Cooperative Training period. Basic level cooperative training has the main aim of providing knowledge to members, administrators as well as other new students who have an interest in the field of entrepreneurship